PENGARUH MODEL KOOPERATIF TIPE CONCEPT SENTENCE TERHADAP KETERAMPILAN MENULIS PARAGRAF KELAS III SD - Lisdyana, Dyah Catur (Universitas Muhammadiyah Surakarta, 2019)
The purpose of this research was to describe the effect of concept sentence cooperative model on the 3rd grade studentâ€™s skill of paragraph writing in SD Cendekia Sidoarjo. The research method used was quantitative experimental method with true-experimental design. The research design used was posttest only control design. The sampling technique was simple random sampling. Technique of data collecting used was paragraph writing test. Technique of data analysis used in this research was normality test (Shapiro wilk test), balance test (F formula), and hypothesis test (independent sample t-test). The result of this research showed that there was effect of concept sentence cooperative model on the 3rd grade studentâ€™s skill of paragraph writing inÂ SD Cendekia Sidoarjo. Based on the comparison with thitung and ttabel is 3,307 2,012.